Serum miRNA biomarker discovery for placenta accreta spectrum. (November 2020) - Chen, Shengzhu; Pang, Dejian; Li, Yongchao; Zhou, Jiayi; Liu, Yunyun; Yang, Si; Liang, Kaixin; Yu, Bolan
Abstract: Placenta accreta spectrum (PAS) disorder is a major cause of maternal and fetal morbidity, and in vitro biomarkers are highly desired in clinic. This study enrolled three phases of 186 pregnant women, including controls, PAS patients, placenta previa (PP) patients, and pre-eclamptic (PE) patients. Initial miRNA array screened 42 out of 768 serum miRNAs in the screening phase, and then validated four miRNAs by quantitative RT-PCR in the training phase and validation phase. Their performance for PAS prenatal screening was analyzed by the receiver operating characteristic (ROC) curve, sensitivity, and specificity. Data validated that four miRNAs (miR-139-3p, miR-196a-5p, miR-518a-3p, and miR-671-3p) were down-regulated in PAS group comparing with controls in three phases of subjects. Except for miR-518a-3p, the expression levels of these miRNAs also were significantly different between the PAS and the group including PP and PE. In addition, these biomarkers demonstrated modest screening efficiency, as the AUC ranged from 0.59 to 0.74, sensitivity 0.54 to 0.80, and specificity 0.62 to 0.76. However, the AUC and specificity can improve greatly (AUC 0.91, specificity 0.92) using a 'diagnostic signature' that combined the four miRNAs and four clinical parameters into one panel. GO and KEGG signaling pathway analysis indicated their target genes were involved in angiogenesis, embryonic development, cell migration and adhesion, and tumor-related pathways. In conclusion, the four miRNAs discovered in this study not only can be used for future non-invasive prenatal PAS screening, but also provide a new experimental basis for future research on PAS etiology. Highlights: Expression of serum miRNAs significantly altered in PAS women. Four miRNAs were constantly down-regulated in PAS women. Target genes were involved in angiogenesis, cell migration and adhesion.